Embodied Community Engagement: Is a University-Based Program in Dialogue and Civic Engagement a Site of Transformational Learning? - Joanna Ashworth; Peter Boothroyd; Charles Dobson; Amy Lang (Adult Education Research Conference, 2010)
Recently, a mid-sized Canadian university launched a unique certificate program in dialogue and civic engagement. Taught by academics and practitioners, the program aims to synthesize diverse concepts and practices from a variety of disciplines related to civic engagement. The goal is to offer learners a mix of conceptual and practical knowledge that empowers them to become civic engagement leaders in their own communities or practice settings.